Measuring nutrition governance in Nepal: A multilayer assessment of institutional and individual capacities and commitment at national, regional and local levels. - Webb, Patrick, 1959- (Tufts University. Tisch Library., 2016)
Dr. Webb explores the multi-faceted nature behind Feed the Future's PoSHAN study and its effectiveness in answering crucial questions on how nutrition governance policy can be best implemented and how to see its change. Delivered on Day 1 of the 2016 NIL Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy